2005
DOI: 10.1073/pnas.0504640102
|View full text |Cite|
|
Sign up to set email alerts
|

Early age-related cognitive impairment in mice lacking cannabinoid CB1 receptors

Abstract: The molecular mechanisms contributing to the normal age-related decline of cognitive functions or to pathological learning and memory impairment are largely unknown. We demonstrate here that young mice (6 -7 weeks) with a genetic deletion of the cannabinoid CB1 receptor performed as well as WT mice, or often better, in a number of learning and memory paradigms, including animal models of skill-learning, partner recognition, and operant conditioning. In contrast, the performance of mature mice (3-5 months) lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 44 publications
4
85
1
1
Order By: Relevance
“…However, this result rules out that the differences in BDNF mRNA levels simply relate to an age-dependent decline in the number of neurons in CB1 À/À mice. 24 In summary, we propose that impaired CB1 receptor signaling, which seems to compromise BDNF expression in the hippocampus, can lead to increased passive stresscoping behaviors in the FST and slightly altered behavioral responses to acute antidepressant treatment. Thus, our results generally support the findings from the human rimonabant phase-III trials reporting a slightly increased percentage of patients with anxiety and depressed mood as compared to placebo controls.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, this result rules out that the differences in BDNF mRNA levels simply relate to an age-dependent decline in the number of neurons in CB1 À/À mice. 24 In summary, we propose that impaired CB1 receptor signaling, which seems to compromise BDNF expression in the hippocampus, can lead to increased passive stresscoping behaviors in the FST and slightly altered behavioral responses to acute antidepressant treatment. Thus, our results generally support the findings from the human rimonabant phase-III trials reporting a slightly increased percentage of patients with anxiety and depressed mood as compared to placebo controls.…”
Section: Discussionmentioning
confidence: 87%
“…13 CB1 receptor-deficient mice share several symptoms with patients suffering from melancholic depression such as, for example, altered responsiveness to reward stimuli, 22 altered neurovegetative functions, 23 a predominance and persistence of aversive memories, 8,9 and possibly neurodegeneration. 24 Furthermore, it was shown by us and others that impaired endocannabinoid signaling can lead to sustained hyperreactivity of the hypothalamic-pituitaryadrenocortical (HPA) axis 23,25 and might also interfere with the proliferation of neural progenitor cells. 26 Human postmortem studies of depressed suicide victims, which have revealed dysregulations of the endocannabinoid system in the prefrontal cortex 27,28 further strengthen the notion of a potential role of the endocannabinoid system in depression.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent work has shown that mature, but not young, CB 1 receptor (À/À) mice display cognitive deficits resembling those seen in aged ( + / + ) mice, suggesting that the endocannabinoid system may serve to protect against age-related cognitive decline (Bilkei-Gorzo et al, 2005). Collectively, these results raise the provocative possibility that facilitation of the endocannabinoid system may represent a novel target for nootropic activity.…”
Section: Discussionmentioning
confidence: 89%
“…And in reality, genetic deletion of CB1 receptors leads to an age-related change in the learning and memory abilities of mice. Young CB1 receptor knockout (CB1 2/2 ) mice showed a superior performance in a broad range of models including object [231] and social recognition tests, in skill and operant learning models [232] as well as enhanced long-term potentiation [233]. The learning ability of 12-month-old CB1 2/2 mice is, however, impaired and this impairment was accompanied by a loss of principal neurons in the hippocampus.…”
Section: Age-dependent Effect Of the Cannabinoid System On Learning Amentioning
confidence: 99%